Factors of cardiopulmonary bypass assistance application in planned off-pump coronary artery bypass surgery - A. V. Rudenko; Ie. A. Nastenko; O. O. Zhurba; O. K. Nosovets; Yu. V. Shardukova; L. S. Fedorova; V. V. Lazorishinetz (Ukrainian Journal of Cardiovascular Surgery, 2017)
Decision-making on the use of cardiopulmonary bypass (CPB) support associated with the analysis of large amounts of patient data, which increases the likelihood of erroneous decisions. Various factors of complications differently compensates by patient’s management protocol application at all stages of cardiac surgery. Their analysis can provide valu-able information for improving the patient’s management protocol and reduce the likelihood of CPB support emergent use.Aim. Analysis of factors of CPB planned and emergent use at off-pump coronary artery bypass surgery.Materials and methods. On the clinical material of 972 patients who underwent CABG without PC support, 178 patients with planned CPB support and 90 patients who underwent an emergent use of CPB assistance the 67 clinical and anamnestic parameters were analyzed.Results and discussion. The NYHA and Strazhesko functional classes is integrated, determined by combination of sev-eral clinical factors, and therefore is highly informative for decision-making on surgery tactics.Decision-making on the use of CPB assistance should take into account the factors, which are the components of these functional classes. The same is concern to corrective therapy application.The necessity for CPB emergent use can originate at simultaneous presence of factors, the frequency of individual oc-currence of each of them is low.Conclusions1. At used protocol of treatment the significant factors influencing the decision-making on the use of CPB assistance are the NYHA and Strazhesko functional classes.2. Additional risk factors may be severe chronic lung disease and crisis course of arterial hypertension.3. The presented analysis of the factors of CPB planned and emergent use makes it possible to carry out the patient’s management protocol correction.